Energy audit of building systems : an engineering approach - Krarti, Moncef (Boca Raton : CRC Press, 2021)
"Updated to include recent advances, the new edition presents strategies and analysis methods for conserving energy and reducing operating costs in residential and commercial buildings. Auditors, managers, and students will find this to be an invaluable resource for their work"--
OCLC-licensed vendor bibliographic record.
Keywords: Buildings -- Energy conservation; Energy auditing; SCIENCE / Mechanics / Dynamics / Thermodynamics; TECHNOLOGY / Construction / Heating, Ventilation & Air Conditioning; TECHNOLOGY / Engineering / Civil